The phenomenon of mystical revelations in the life of the mystic Katarzyna Szymon - Rachwalik, Walter (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
Katarzyna Szymon’s life, from childhood to old age (1907-1986), was marked by suffering and numerous graces and mystical phenomena, including the charism of visible stigmata. She gave herself to God by making a religious vow to live in the virtue of virginal purity. The example of her mystical path reflects the Church’s certainty, based on the Gospel, that in the eyes of God the faithful imitating the humility of the Sacred Heart of the Savior receives the highest recognition (cf. Mt 11:25-30).